Women's Experiences of Breastfeeding-Related Pain. Issue 2 (March 2019) - Jackson, Kimberley T.; Mantler, Tara; O'Keefe-McCarthy, Sheila
Abstract: Purpose: Breastfeeding-related pain is commonly experienced early in the postpartum period and is an important contributor to breastfeeding cessation, yet little is known about what this pain means to women and how it is experienced. The purpose of this study was to gain a better understanding of the phenomenon of breastfeeding-related pain, how women experience this pain, and the meaning it holds for them. Study Design and Methods: Interpretive descriptive methods and inductive content analysis were used. Women were recruited using purposive sampling with a snowball approach. Data were collected via one-to-one interviews using a semistructured interview guide with postpartum women having experienced breastfeeding-related pain in the past 2 months. Results: Fourteen postpartum women who met inclusion criteria were interviewed. They were predominantly Caucasian, well educated, and had greater than average Canadian annual household incomes. The dominant emerging discourse revealed three key themes: (a) interplay between breastfeeding pain and context, (b) action enablers and/or barriers, and (c) breastfeeding outcomes. Clinical Implications: Breastfeeding-related pain is an unpleasant sensory and affective experience for women during the postpartum period. Availability and accessibility of breastfeeding supports are essential to enable women to achieve their breastfeeding goals. Providing anticipatory guidance may help women to cope more effectively with their breastfeeding-related pain. Abstract : Pain related to breastfeeding can have a negative effect on breastfeeding duration and the mother-baby relationship. In this study women describe their experiences with breastfeeding-related pain including support and barriers. These data can be helpful in planning a discussion of what to expect when breastfeeding with new mothers during the prenatal and postpartum periods.